Neuro-rights in Labor Law from the reform of Law 21.383 and its projection - Padilla Parga, Roberto (Revista Chilena de Derecho y Tecnología, 2024)
With the reform of Law 21.383, an unprecedented global phenomenon occurs in the Chilean legal system through the constitutional recognition of neurorights. Considering that neurotechnologies project an influence on social life and that work plays a central role in it, it is appropriate to ask if there is any kind of effect of this right in the workplace and what can be said regarding the inclusion of neurorights in Labour Law. This text argues against the idea of proceeding immediately to the adoption of this proposal in the labor field in favor of exploring the options already existing in the legal system of the branch, those that protect the same legal rights that would be sought to be protected through this new category of rights, subtracting contribution.